2020
DOI: 10.1186/s13099-020-00377-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of the VP1 region of enterovirus 71 strains in China

Abstract: Background: Enterovirus 71 (EV71) is the most commonly implicated causative agent of severe outbreaks of paediatric hand, foot, and mouth disease (HFMD).VP1 protein, a capsid protein of EV71, is responsible for the genotype of the virus and is essential for vaccine development and effectiveness. However, the genotypes of EV71 isolates in China are still not completely clear. Methods: The VP1 gene sequences of 3712 EV71 virus strains from China, excluding repetitive sequences and 30 known EV71 genotypes as refe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…In addition, the major circulating strains of EV-A71 were genotype C4a in China [ 29 , 35 ]. The widespread use of the EV-A71 vaccines might affect the landscape of other genotypes in circulation, but the sub-genotype switch of EV-A71 has not been observed or reported in China [ 36 , 37 ]. Further studies on EV-A71 genome characteristics based on the national surveillance are still useful and essential for monitoring the emergence of new variants and preventing HFMD outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the major circulating strains of EV-A71 were genotype C4a in China [ 29 , 35 ]. The widespread use of the EV-A71 vaccines might affect the landscape of other genotypes in circulation, but the sub-genotype switch of EV-A71 has not been observed or reported in China [ 36 , 37 ]. Further studies on EV-A71 genome characteristics based on the national surveillance are still useful and essential for monitoring the emergence of new variants and preventing HFMD outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of the strains collected in the provinces of South Vietnam formed a monophyletic cluster with the nucleotide sequences of EV-A71 viruses circulating in some provinces of China during 2016-2018 and in Germany during 2018-2019 [20,35]. The highest homology (99.2-99.9%) of the nucleotide sequences of majority of Vietnamese strains belonging to this genetic group was revealed with the strains identified in patients with HFMD and AFP from the Chinese province of Yunnan in 2017-2018.…”
Section: Figure 1 Phylogenic Relationship Between Ev-a71 Strains Of Genotype C4 Identified In Russia and Vietnammentioning
confidence: 99%
“…Strain VND18/227 identified in one HFMD patient, who had a complicated clinical form of the disease, was very close to German EVA71 strains (99.2–99.4% of homology) of the C4 genotype. All these viruses represented a separate genetic group and had a high relationship with EVA71 strains detected in the Guangdong province of China in 2017 [ 12 ]. EVA71 viruses of the C4 genotype revealed in HFMD and AFP cases from our study were different from viruses revealed in 2003–2005 and 2011–2012 during HFMD outbreaks in South and North Vietnam [ 9 , 13 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Enteroviruses A-D species genus Enteroviruses family Picornaviridae are associated with human enteroviral infection. Enteroviral infection (EVI) is characterized by a wide diversity of clinical forms, including enteroviral meningitis, meningoencephalitis, hand-foot-and-mouth disease (HFMD), and other clinical manifestations [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%